INNOVATION IN STAGE DESIGN THROUGH VIRTUAL REALITY AND IMMERSIVE TECHNOLOGIES - N, Nivetha; B, Damodaran; V, Dhanalakshmi; P.V., Hari Hara Subramanyan; K, Parimala; Jayesh, Dr. Raghavendra (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The stage design is a vital factor when it comes to creating the visual, spatial, and emotional significance of performing art productions. Historically, theatrical scenes have been based on physical sets, light, and set design to facilitate the narration and improve the experience of the audience. Nonetheless, new possibilities of changing the stage design have been introduced by the recent technological developments of digital and immersive technologies. This paper discusses how Virtual Reality (VR) and immersive technology can be used to achieve stage design and performance production innovation. The study looks at the potential of VR in aiding virtual stage prototyping, digital scenography, interactive stage settings and the immersion of an audience. Based on the literature review and assessment of the current practices of stage design, the research identifies the benefits of VR-based design methods, which are better visualization, increased creative ability, improved teamwork in the production teams, and more immersive experiences of the audience. There is also a comparative study of the conventional stage design techniques and VR-oriented ones aimed at assessing the difference in the working process, efficiency of production, creative opportunities, and experience of the audience immersion. Moreover, the paper suggests a theoretical framework of the incorporation of VR technologies in stage design procedures, showing the combination of artistic creativity and technology improvement to create the immersive setting in the performances. The samples of immersive theatre plays prove that digital technologies may widen the frames of the stage design and narrative. The paper also covers the main issues related to immersive technologies, such as technical infrastructure, budget, training and development of skills, and ethical issues related to digital performance environments. The results indicate that there will be a great potential in terms of creative and participatory ability of performing arts with a hybrid solution that incorporates the use of conventional stagecraft and immersive technologies. The study also ends with the identification of the future trends in immersive stage design, such as artificial intelligence, extended reality, and metaverse-based performance platforms integration.